2010
DOI: 10.1088/2043-6262/1/3/035006
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption ability of Cr(VI) on sawdust–polyaniline nanocomposite

Abstract: The results of this study of sawdust-polyaniline nanocomposite synthesized by a chemical method for Cr(VI) treatment in the environment are presented. Cr(VI) adsorption on a composite was determined by colorimetry. The results showed that sawdust-polyaniline composite synthesized with an aniline : sawdust ratio equal to 0.5 had an adsorption degree of 21.4 mg g −1 and adsorbed nearly 99% of the Cr(VI) after 2 h. The composite could be used for the adsorption of Cr(VI) from waste water. The Cr(VI) adsorption ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Li et al (2014) utilized PANI synthesized on filter paper with a porous structure to remove metal ions or low molecular weight materials, and Cr(Ⅵ) removal by this composite was effective under high temperature and low pH conditions. Mansour et al (2011) and Phan et al (2010) used a PANI coating on sawdust to remove Cd(Ⅱ) and Cr(Ⅵ). Phan et al (2010) reported that the Cr(Ⅵ) adsorption of the composite was affected by pH, and the adsorption rate was fastest during the first half hour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2014) utilized PANI synthesized on filter paper with a porous structure to remove metal ions or low molecular weight materials, and Cr(Ⅵ) removal by this composite was effective under high temperature and low pH conditions. Mansour et al (2011) and Phan et al (2010) used a PANI coating on sawdust to remove Cd(Ⅱ) and Cr(Ⅵ). Phan et al (2010) reported that the Cr(Ⅵ) adsorption of the composite was affected by pH, and the adsorption rate was fastest during the first half hour.…”
Section: Introductionmentioning
confidence: 99%
“…Mansour et al (2011) and Phan et al (2010) used a PANI coating on sawdust to remove Cd(Ⅱ) and Cr(Ⅵ). Phan et al (2010) reported that the Cr(Ⅵ) adsorption of the composite was affected by pH, and the adsorption rate was fastest during the first half hour. The functional groups in PANI have been reported to have a strong affinity for heavy metals such as Cr(Ⅵ) (Eisazadeh 2007;Zhang et al 2010;Bhaumik et al 2012;Krishnani et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that rice husk [7], olive stone [8], clay minerals [9][10][11][12], used tea leaves [13], wheat straw [14], banana peel [15,16], chitin and chitosan [17] as a good adsorbent, because these are easily available and less polluting substances. It was reported that metals are attached onto the surface of adsorbent in the adsorption process [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Recently the scientists are focused their attention on the synthesis of biocomposites, which are consisted of residual vegetation and polymeric substances. [22][23][24] It is known that for the treatment of different kinds of wastewaters constructed wetland systems are used. In them different macrophytes are growing -Phragmites australis, Typha latifolia, etc., which have the ability to extract and accumulate a variety of contaminants from the treated water.…”
mentioning
confidence: 99%